Determinant Factors in Prosocial Behavior Education in The Industrial Era 4.0 - Uly Natiqotul Ashfa; Nur Khoiri; Widodo Supriyono (Institut Agama Islam Negeri Jember, 2022)
Humans are social creatures who essentially need other humans in their environment. To achieve the necessities of life, humans interact in their social environment. They cooperate with other people, make friendships, sympathize, or vice versa, such as doing the fierce competition, selfishness, and others. These actions are nothing but to get everything you want. Their actions are sometimes in accordance with social norms, sometimes also contrary to them. Advances in information and communication technology in the era of the digital revolution have hurt human behavior. They are more likely to be individualistic and materialistic and to have antisocial attitudes. From these problems, prosocial behavior education is needed to develop individuals who return to their nature as social beings. This research is library research that analyzes several relevant papers. The discussion of the contents of the discussion describes prosocial behavior education in the Industrial Era 4.0, aspects of prosocial behavior, and the determinant factors. The conclusion is that the determinant factors in prosocial behavior education in the Industrial Era 4.0 can be done by intensely conducting guidance such as if? Al-Qur'?n guidance, then with the presence of Islamic spiritual intelligence in the individual and parenting patterns.